Teoria da construção do vínculo em saúde em um serviço de saúde suplementar - Viviane Gonçalves Barroso (2017)
The scientific production has accompanied the movement of valorization of the integral approach and the subjectivity, in the confrontation of the reductionism to the biological aspects of the disease, and of the logic and effects of the society of consumption, that reached the health field. In this sense, the bond is a phenomenon that is related to the subjective aspects that contribute to adherence to care. It wasdefended the thesis that the link in the health services is built in a relational process that occurs in a multifactorial way, through social, organizational, technical and subjective aspects, and that presents singularities pertinent to the Supplementary Health System, even though Can be replicated. The objective of this study was to develop theorization about the construction of the link in health, from the perspective of the participants, in a Supplementary Health service. Guided by the Comprehensive Care Model and the Family Health Strategy, the Bank of Brazil Staff Assistance (CASSI) develops experience in Brazilian Supplementary Health and has established itself as a privileged institution for research. Thirty-three participants, aged between 19 and 97 years, were interviewed, both men and women, who were identified as being tied to CASSI's services in Belo Horizonte, Juiz de Fora, Montes Claros, Uberlândia and Uberaba, in the State of Minas Gerais. The Grounded Theory and Symbolic Interactionism were the methodological and theoretical references of the qualitative study. The Theory of the construction of the bond in health, result of this study, was constituted from concepts and subconceptions, organized into categories and subcategories. The first category, named Belonging, deals with the references that lead to trust in the care institution, which a priori influence the demand and care interactions in the services. The second, named Reception, addresses the trust in the service, which stems from the availability to the service and the answers obtained. The trust in the service feeds the trusted care institution and enhances trust in care.The third category, Care in Act, results from the articulation of personal and technical attributes to the oriented and structured way of doing in services, which leads to trust in care and feeds confidence in services and the care institution. The concepts that deal with the relations that lead to the establishment of the bond are not articulated in a linear way. It was evidenced subsidies that can contribute to the reorientation of theorganization of the assistance proposal and the health practices. We highlight elements described related to the conjunctural scenario of the reality studied, differing from the public sector. The results lead to reflections that raise new hypotheses that complement or reinforce the presented plot.